Rekonstruksi Pengaturan Ganti Kerugian Pengadaan Tanah Untuk Kepentingan Umum Yang “Orangnya Tidak Diketahui Keberadaannya” Dalam Perpektif Perlindungan Hukum - Bernada, Yaffed Septian (Journal Evidence Of Law, 2025)
This study aims to examine and reconstruct the regulation of compensation in land acquisition for public purposes when the rightful party to the land is unknown, in order to ensure fair and certain legal protection for all parties. Essentially, land availability and development are closely related. Based on the principle of the “Right to Control by the State” and the “social function of land,” the State is authorized to acquire land from the public through the mechanism of land rights revocation or land acquisition to meet land needs. The method used in this study is normative legal research, focusing on analyzing legal issue resolution based on existing legal principles and doctrines. In doing so, the State is obliged to provide “adequate and fair” compensation to the entitled party or their representative. Every process in land acquisition must be carried out through deliberation to reach an agreement between the agency requiring the land and the affected community or the rightful party. The findings show that the regulation of compensation for public purposes where the rightful party is unknown remains weak in terms of legal certainty and protection of rights. Therefore, a regulatory reconstruction is necessary by clarifying procedures for identification, management of consigned funds (consignment), and legal protection for unidentifiable landowners.